Comparative Evaluation and Demonstration of Field Pea Production Practices in Intermediate Altitudes of Northeastern Amhara, Ethiopia - Ademe Mihiretu; Netsanet Assefa (Turkish Journal of Agriculture: Food Science and Technology, 2019)
On-farm evaluation and demonstration of different field pea production packages (IFPP, LFPP and LFTP) was carried out for two cropping seasons across districts on seventeen sites in Northeastern Amhara region. The objectives of the experiment were to evaluate the performance of different field pea technologies and to demonstrate the package to the farmers and the extension personnel then to collect feedback from participants. The experiment was conducted by comparing improved variety with its full package along with the local variety under full package practice and farmers’ traditional practice. The agronomic, economic and farmers’ preference analysis clearly indicated that the improved technology is superior to the local variety under full package and farmers’ practice. The average mean grain yields of the improved practices (IFPP and LFPP) were 1901.7 and 1428.3 kgha-1in Dehana, while 1933.3 and 1520 kg ha-1 in Sekota district, respectively. Therefore, the improved field pea technology had a yield advantage of 33.2% and 91.8% respectively from the local cultivar under improved and farmers practice in Dehana. However, the improved technology had 27.2% and 94.6% yield advantage over the local with improved and farmers practice in Sekota, respectively. The marginal rate of return for improved technology in Dehana and Sekota districts was 857.2 and 1344.7%, respectively. Farmers perceived the higher yield potential of the improved technology as a result many of them showed great demand for improved field pea technology. So that pre-scaling up of the improved variety with its production package is recommended to similar agro ecologies.